Methods of appropriation of coordinates, determination of orientation and visualization of moving objects on cartographic background in the real time». - Васюхін, М. І.; Гулевець, В. Д.; Бойко, О. Л. (Problems of Informatization and Control, 2009)
The method of determination of location, appropriation of coordinates, determination of orientation and visualization on the screen of the systems of displaying of dynamic objects symbol, moving in near-earth space, is offered